PENINGKATAN MOTORIK KASAR ANAK MELALUI PERMAINAN TRADISIONAL PETAK UMPET DI TAMAN KANAK-KANAK - Ashar Ashar; Inrawulan Inrawulan (Universitas Negeri Makassar, 2021)
This study applies traditional games that can improve gross motor skills of early childhood, in this case the hope is that it uses a fast and appropriate way of traditional games, so this study aims to determine the level of gross motor skills of children through the traditional game hide and seek group B in kindergarten. Az-zahra. The type of research used is classroom action research. held at TK Az-zahra Kec. Biring Romang, Makassar City, with the number of children studied, namely 15 children, 7 boys and 8 girls. Data collection techniques used are observation and documentation. The results obtained after doing the research, the level of gross motor skills of children with the data obtained in the first cycle only reached 84%, while in the second cycle it has reached 97% with the very well developed category.